Huemul Hippocamelus bisulcus - problemy ochrony ginacego jelenia z patagonii - Gizejewski, Zygmunt (2017)
Huemul Hippocamelus bisulcus. Problems of protection of the endangered deer from Patagonia Patagonian hemul (Hippocamelus bisulcus) is a member of the deer family (Cervidae) classified as an species. The size of its population, estimated at 350?500 heads in Argentina and at 1000 in Chile, is distributed in over 100 family groups. Taking into account the gradually decreasing number of specimens, it is necessary to establish a captive breeding center. Besides reproduction and reintroduction to the natural environment, the center will help also to conduct scientific investigations on this poorly known species. Tamed animals reared on the bottle will allow to collect semen using artificial vagina, and would provide an opportunity to establish a live semen bank protected in liquid nitrogen (LN2), as a reserve of genes.